1978
DOI: 10.1366/000370278774330847
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Vibration Spectra. XX. Infrared and Raman Spectra of BaCl2•2H2O and BaCl2•2D2O

Abstract: The infrared absorption and laser Raman spectra of BaCl2·2H2O powder and single crystals as well as BaCl2·2D2O, partially deuterated, and isotopically dilute samples have been analyzed in the range from 30 to 4000 cm−1. A revised interpretation of the observed water bands is given. The influence of the bond angle of the H2O molecules both on Raman intensity of the water modes and frequency shift of the bending fundamentals is discussed. The librational modes are assigned with regard to isotopic shifts and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The latter is usually referred to as the association band [60] because of its original assignment to the transition (v2 + vL -vT). More recent work on solid water in crystalline hydrates [61] would indicate that v2 + vR (R, librational modes) may be preferred. A summary of the bands involved is given in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is usually referred to as the association band [60] because of its original assignment to the transition (v2 + vL -vT). More recent work on solid water in crystalline hydrates [61] would indicate that v2 + vR (R, librational modes) may be preferred. A summary of the bands involved is given in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, some of these shoulders do become evident at much lower concentrations of surfactant and are, in all probability due to the perturbation of water molecules due to cation or anion binding[61,62].…”
mentioning
confidence: 99%
“…[30] Jain et al [31] proposed that the wavenumbers of the rocking, twisting and wagging vibrations should follow the sequence ρ > τ > ω, whereas Makitova et al [7] suggested the order ρ > ω > τ. The assignment made by Lutz et al [25] located the wagging, twisting and rocking vibrations in 610-725, 490-570 and 410-545 cm −1 regions, respectively. These results were based on the deuteration of the studied materials.…”
Section: Raman Spectramentioning
confidence: 97%
“…[21 -24] Static and dynamic models of the interactions between the water molecules in the unit cell have been considered. [25,26] The librational modes of the water units have been found in the regions 660-780 and 340-430 cm −1 , both in the IR and Raman spectra. [27 -29] The assignment of other external vibrations of the water units in the hydrates is not consistent.…”
Section: Raman Spectramentioning
confidence: 99%
“…This splitting is caused by the possibility of different structural arrangement of the H and D atoms in salt hydrates with asymmetric water molecules' and was first found in the spectra of BaC12.2H20. 3 The H D O librational fundamentals can be observed as sharp distinct bands only in isotopically dilute samples, if overlap with other bands is absent. In samples with higher content of H D O molecules, broadening and additional splittings of the H D O librations, not fully resolved in the spectra, take place caused by dynamic coupling of the vibrations.…”
Section: Librational Modes Of the Water Moleculesmentioning
confidence: 99%